The last gay man on Earth - Driessen, Ype (Street Noise Books, 2023)
A delightful graphic memoir told in photographs. This book will warm your heart and make you laugh out loud! Ype is a gay man living in Amsterdam with his boyfriend Nico. When asked by Nico to accompany him on a work trip to America, Ype must confront his deep fear of flying. While doing so, Ype finds he also has to come to terms with his social and sexual anxieties, his neurotic nature, and a serious case of imposter syndrome. What follows is a moving and deeply personal story, filled with humor as well as drama --surprising, honest, and unforgettable. Ype embarks on an adventure that leads him to his ultimate fantasy: being the last person on earth. Encouraged by a sentient robot vacuum cleaner called Chupi, he finds out what it really means to be true to yourself
"The Last Gay Man on Earth was originally published in Dutch as Het nadeel van de twiijfel by Uitgeverij Luitingh-Sijthoff in the Netherlands in 2020"--Title page verso
Keywords: Mann; Fotoroman; Neurotiker; Homosexueller; Sozialangst; Driessen, Ype / 1979- / Comic books, strips, etc; Cartoonists / Netherlands / Biography / Comic books, strips, etc; Gay men / Biography / Comic books, strips, etc; Homosexuels masculins / Biographies / Bandes dessinées; COMICS & GRAPHIC NOVELS / LGBTQ+; COMICS & GRAPHIC NOVELS / Dystopian; COMICS & GRAPHIC NOVELS / Nonfiction / Biography & Memoir; Cartoonists; Gay men; Netherlands; Autobiographical comics; Comics (Graphic works); Fotonovelas; Gay comics; Graphic novels; Humorous comics; Queer comics; Comic